Multiphase Microreactors Based on Liquid–Liquid and Gas–Liquid Dispersions Stabilized by Colloidal Catalytic Particles. (1st October 2021) - Dedovets, Dmytro; Li, Qingyuan; Leclercq, Loïc; Nardello‐Rataj, Veronique; Leng, Jacques; Zhao, Shuangliang; Pera‐Titus, Marc
Abstract: Pickering emulsions, foams, bubbles, and marbles are dispersions of two immiscible liquids or of a liquid and a gas stabilized by surface‐active colloidal particles. These systems can be used for engineering liquid–liquid–solid and gas–liquid–solid microreactors for multiphase reactions. They constitute original platforms for reengineering multiphase reactors towards a higher degree of sustainability. This Review provides a systematic overview on the recent progress of liquid–liquid and gas–liquid dispersions stabilized by solid particles as microreactors for engineering eco‐efficient reactions, with emphasis on biobased reagents. Physicochemical driving parameters, challenges, and strategies to (de)stabilize dispersions for product recovery/catalyst recycling are discussed. Advanced concepts such as cascade and continuous flow reactions, compartmentalization of incompatible reagents, and multiscale computational methods for accelerating particle discovery are also addressed. Abstract : This Review summarizes recent progress in liquid–liquid and gas–liquid dispersions stabilized by solid surface‐active colloidal particles (emulsions, foams, bubbles, marbles, bijels) as microreactors. These new systems constitute original platforms for reengineering multiphase reactors towards a higher degree of sustainability.